Between high ambition and pragmatism: Proposals for a reform of fiscal rules without treaty change. expert study commissioned by the European Economic and Social Committee (EESC) - Sebastian Dullien; Christoph Paetz; René Repasi; Andrew Watt; Sebastian Watzka (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2022)
This study examines major reform proposals of EU fiscal rules from an economic and legal perspective. We disassemble the reform proposals in their components and analyse them in their specific proposed form in comparison, thereby shedding light on what is legally possible, economically sensible, and which parameters are to be looked at when putting together a final reform package. We show that quite far-reaching reforms of EU fiscal rules are feasible without treaty change as current secondary legislation restricting member states' fiscal policies are much more detailed and often much stricter than the original treaty provisions. Especially proposals that shift the current rules towards expenditure rules and which provide for limited borrowing for public investment can be implemented by changing secondary legislation only, provided the parameters are set such that the original deficit thresholds in the treaty are not violated. The same holds for measures lending greater importance to the Macroeconomic Imbalance Procedure. Increasing the reference value on the debt ratio would require a unanimous vote in the Council after consultation of the European Parliament and the ECB. Proposals that try to shift fiscal rules from rules to standards and focus on empowering independent bodies are instead legally much more difficult to reconcile with the EU treaties.
Keywords: 330; European Economic and Social Committee (EESC); fiscal rules; Fiskalregeln; EU; Eurozone; Economic Governance